MAINSTREAMING OF RELIGIOUS MODERATION IN INDONESIAN ISLAMIC EDUCATIONAL INSTITUTIONS - Susiawati, Iis; Royani, Ahmad; Mardani, Dadan; Alhaq, Muhammad Faiz (Hunafa: Jurnal Studia Islamika, 2023)
Islam actually exists as rahmatan lil 'alamin. Understanding of Islam has a balance of reasoning and realistic thinking, and refers to various sources that are comprehensive and consistent. Education is a means of human regeneration to deal with the development of an intellectual civilization that continues to be dynamic by promoting improvements for the good of human life itself. This article uses a descriptive qualitative approach with a literature study data collection technique related to religious moderation in the realm of education. The data is analyzed inductively after first being categorized according to the need for data synchronization. The results of the study prove that mainstreaming religious moderation in Islamic educational institutions in Indonesia is an urgency for a religious and state foundation in this republic. The Republic of Indonesia has a rich culture and various differences that must be preserved in a unified nation based on Pancasila and the 1945 Constitution which was declared by the founding fathers of this nation.